PENGARUH METODE EKSTRAKSI DAN POLARITAS PELARUT TERHADAP KADAR FENOLIK TOTAL DAUN KERSEN (Muntingia calabura L): Effect of Extraction Method and Solvent Polarity on Total Phenolic Content of Cherry Leaves (Muntingia calabura L) - Wina Yulianti; Gilang Ayuningtyas; Rina Martini; Ika Resmeiliana (IPB University, 2020)
ABSTRACTThe method of extraction and the type of solvent used during extraction will influence effectiveness of the extraction and compound extracted. The aim of this research was determined the effect of extraction methode and solvent polarity on total phenolic content of cherry leaves (Muntingia calabura L). Extraction of cherry leaves used maceration and soxhelation methods with ethanol and chloroform as solvents. The total phenolic contain was determined by visible spechtrophotometer at 765 nm. It has been showed that the soxhletation method was a higher yield value than the maceration methods with the highest yield value showed by ethanol extract, it was 13,29% w/w. Otherwise maceration method showed a higher total phenolic contain with the highest total phenolic contain showed by ethanol extract, it was 10,70% GAE.